Peningkatan Literasi Sembelih Halal dan Manajemen Qurban Melalui Pelatihan Partisipatif di STIE Ganesha - Sitti Aliyah Azzahra; Nurhayati Nurhayati; Jayaun Jayaun; Suharmanto Suharmanto; Suhermanto Suhermanto; Tohiroh Tohiroh; Syafran Nurrahman; Sutariyono Sutariyono (BADAN PENERBIT STIEPARI PRESS, 2025)
The implementation of qurban worship in accordance with Islamic law still faces various challenges, particularly regarding public understanding of proper halal slaughter procedures and effective qurban management. This community service activity aims to enhance the religious literacy of STIE Ganesha’s academic community through participatory training on halal slaughter and qurban management. The training was held on May 31, 2025, at the STIE Ganesha Hall, involving lecturers, students, and campus staff. The methods included delivering fiqh qurban material, technical demonstrations of slaughtering, field simulations, and reflective discussions based on case studies. The results of the training showed a significant improvement in participants’ understanding of halal slaughter principles and their technical abilities in managing qurban in a trustworthy, efficient, and Sharia-compliant manner. These findings indicate that a participatory training approach effectively strengthens religious literacy and develops competent, religious, and responsible qurban practitioners. The implications of this activity highlight the importance of continuing halal education programs within the campus environment as part of the institution’s contribution to strengthening religious practices based on knowledge, values, and adherence to Islamic law.